Pelatihan Pengelola Posyandu Prima Di Kampung Pujo Kerto Kecamatan Trimurjo Lampung Tengah - Imam Santosa; Daria Br. Ginting; Arie Nugroho; Titi Astuti (CV. Multi Kreasi Media, 2023)
Posyandu is the spearhead in the Village in its position as a Village Community Institution (LKD). Its activities are expanded to include Health Services in collaboration with Sub-Puskesmas (Pustu) and Community Health Centers. The program is based on a holistic approach that includes disease prevention, health care, and improved nutrition. This program involves local communities and posyandu cadres in health care efforts, monitoring children's growth and development, and promoting healthy health practices. The situation analysis above is the basis for the formation and training of prime posyandu managers in PujoKerto village. The aim of the community service activities for the Tanjungkarang Health Polytechnic PPDM scheme in Pujo Kerto Village, Trimurjo District is to socialize prime posyandu, sign cooperation and establish prime posyandu, and train cadres of prime posyandu managers. The methodology for community service activities is as follows: Preparation, Implementation and Evaluation. The results of the activities are as follows: The socialization of prime Posyandu has been carried out, cooperation has been established, marked by the signing of cooperation, the formation of a prime posyandu organization, and the provision of training for prime posyandu management cadres.